Embodied design: Design inspiration and mood improvement depend on perceived stimulus sources and predict satisfaction with an immersion experience. Issue 2 (2nd April 2020) - So, Chaehan
ABSTRACT: This paper investigates how the immersion into a real-world user context influences design students' design inspiration and mood improvement. To this aim, the present study analyzed the perception of 16 design students who immersed themselves into a dance studio and compared it with the external evaluation of 74 professional designers. Results indicate that (a) design students can attribute the immersion experience to multiple stimulus sources; (b) the mood improvement and design inspiration induced by the immersion experience predict their satisfaction level; and (c) the design inspiration induced by the immersion experience can be recognized by external observers. These findings can be harnessed for leveraging designers' user research effectiveness by embedding it in an immersion experience.